ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, PROFITABILITAS, KESEMPATAN INVESTASI DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2013) - Vido Agnova; Dul Muid (Diponegoro Journal of Accounting, 2015)
Company in business wants to increase the value of the company. This is because the value of the company reflects the performance of the company and may affect investor perception of the company. This study aimed to analyze the effect of: (1) managerial ownership, (2) profitability, (3) investment opportunities, (4) the policy of debt to the value of the company on manufacturing companies listed in bei 2010-2013. The value of the company is willing to pay the price by potential buyers when the company is sold. Managerial ownership is a stock company owned by the management company. Profitability is an important factor in determining the capital structure. With large retained earnings, the company would prefer to use retained earnings before using debt. Investment opportunities in enterprise management decisions in the selection of an investment that will be able to choose one or more investment alternatives are considered the most profitable. a debt policy measures taken by the company to finance through debt.Data collection techniques in this research is the study documentation. Data to be studied in this research is secondary data that is quantitative. The data used in this research is secondary data from annual reports obtained from the Indonesian Capital Market Directory (ICMD) 2010-2013. The analysis method used in this study is multiple regression. The population in this study were all manufacturing companies listed in Indonesia Stock Exchange in 2010 - 2013. The sampling method used in this research is purposive sampling method. The number of samples taken in this study as many as 32 companies.From the test results showed that managerial ownership and significant negative effect on the value of the company. While profitability and significant positive effect on firm value. Variable investment opportunity no significant effect on the value of the company. From the test results can be seen that the debt policy and significant positive effect on firm value.